Bankruptcy reform - American Enterprise Institute for Public Policy Research (Washington : American Enterprise Institute for Public Policy Research, 1978)
The book examines the major provisions of proposals for bankruptcy reform introduced in the 95th congress
Includes bibliographical references.
obn25/01/2019
Loans
Keywords: Bankruptcy